SP0062 Fibromyalgia: evidence for a central nervous system disorder. (1st June 2001) - Bradley, L
Abstract : This presentation reviews evidence from several studies in our laboratory regarding central factors associated with abnormal pain sensitivity in fibromyalgia (FM). We have found that, compared to healthy controls, clinic patients with FM and community residents who meet criteria for FM but have not consulted a physician (FM non-patients) display significantly lower pain thresholds in response to pressure stimulation and exhibit significantly higher cerebrospinal fluid (CSF) levels of substance P. In addition, during exposure to suprathreshold levels of pressure stimulation, controls and FM patients differ in changes in brain regional cerebral blood flow (rCBF). That is, controls show significant rCBF increases in the contralateral thalamus, somatosensory cortex, and the anterior cingulate cortex, whereas patients with FM show significant and bilateral increases in rCBF in these brain structures. Finally, patients with FM show greater cardiovascular responses to stress than controls. Moreover, stress produces greater increases in thermal pain unpleasantness ratings among FM patients compared to controls. Together, these findings indicate that FM patients show abnormal central processing of nociceptive stimuli that tends to be exacerbated by stress. We plan to determine whether the effects of stress on pain unpleasantness in FM (a) are associated with abnormal rCBF changes in the anterior cingulate cortex; and (2) may be mediated by abnormal cortisol release or cytokine production. References: Aaron LA, Bradley LA, Alarcon GS, et al . Psychiatric diagnoses in patients with fibromyalgia are related to health care-seeking behavior rather than to illness. Arthritis Rheum. 1996;39:436–45 Bradley LA, Alarcon GS. Fibromyalgia. In: Koopman WJ, ed. Arthritis and allied conditions : a textbook of rheumatology. 14th edn. Baltimore, MD: Williams & Wilkins, 2001 Bradley LA, McKendree-Smith NL, Alarcon GS. Pain complaints in patients with fibromyalgia versus chronic fatigue syndrome. Curr Rev Pain 2000;4:148–57 Bradley LA, McKendree-Smith NL, Alberts KR, Alarcon GS, Mountz JM, Deutsch G. Use of neuroimaging to understand abnormal pain sensitivity in fibromyalgia. Curr Rheumatol Rep. 2000;2:141–8 Bradley LA, Sotolongo A, Alberts KR, et al . Abnormal regional cerebral blood flow in the caudate nucleus among fibromyalgia patients and non-patients is associated with insidious symptom onset. J Musculoskeletal Pain 1999;7:285–92 Mountz JM, Bradley LA, Modell JG, et al . Fibromyalgia in women: abnormalities of regional cerebral blood flow in the thalamus and caudate nucleus are associated with low pain threshold levels. Arthritis Rheum. 1995;38:926–38 Pillemer SR, Bradley LA, Crofford LJ, et al . The neuroscience and endocrinology of fibromyalgia. Arthritis Rheum. 1997;40:1928–37